PENINGKATAN KEMAMPUAN REPRESENTASI MATEMATIS MAHASISWA MENGGUNAKAN MEDIA PROGRAM GEOGEBRA PADA MATA KULIAH GEOMETRI TRANSFORMASI - Anggun Badu Kusuma; Eka Setyaningsih (Khazanah Pendidikan, 2015)
This research aimed at improving the mathematically representation skill of class A semester IV students of mathematics education study program Muhammadiyah Purwokerto University in academic year 2013/2014 in Transformation Geometri subject using Geogebra Program media. This research belongs to action research consisting of planning, implementing, observing, and reflecting. The data analysis used was quantitative and qualitative descriptive analysis. The research showed that in the first cycle, the number of students who got the minimal score 75 was 29 students of 40 who were present or 72,5% of the present students whereas, in the second cycle the students who got the minimal score 75 were 33 of 38 who were present or 86,84%. This result shows that the learning process using Geogebra media succeeded to improve the students mathematically representation skill. Keywords: action research, geogebra program, mathematically representation